The Transformative Potential of Social Theatre Experience: “Taksai. Direction – Kaunas” Audience Reflections - Toleikytė, Uršulė; Petružytė, Donata (Socialinė teorija, empirija, politika ir praktika, 2026)
This study contributes to a broader understanding of social theatre as a multidimensional practice which closely links artistic and social dimensions, potentially generating meaningful experiences for audiences and fostering transformation. The article examines the transformative effect of social theatre, based on the performative tour Taksai [local slang for ‘taxis’]. Direction – Kaunas. The aim of the research is to reveal how audiences experience social theatre and what significance this experience has for transformation. The study used semi-structured interviews with 11 participants (audience members) and analyzed the data by using reflective thematic analysis, following Braun and Clarke (2022).The analysis of the results reveals that participation in this social theatre led to a multi-layered transformation, affecting personal cognitive, emotional, and behavioral levels. Participants in the performative tours were not just passive observers but rather active contributors to the theatrical experience. This involvement led to transformations, including reflection on personal beliefs, stereotypes, and emotional responses. Authentic stories shared during the tour enabled the participants to reconsider their own life experiences, perceive difficult personal histories as meaningful, and develop a sense of empowerment. The theatre experience also created a safe space for trying new behavior, stepping outside social norms, and experiencing one’s own agency. Importantly, the participants expressed a renewed sense of hope – believing in the potential for both personal and collective change. The findings align with the theories of Freire and Boal, showing that social theatre can serve as a performative, educational, and therapeutic practice. It not only deepens self-awareness but also helps destigmatize marginalized experiences and restores individuals’ relationships with their social environment, while fostering a sense of agency and relational interconnection.
Keywords: social theatre; social arts; transformation; P. Freire; A. Boal